(untitled) (INCH : Journal of Infant and Child Healthcare, 2023)
Maternal mortality rate in Indonesia has increased in 2019-2020. The most common cause of MMR is bleeding and the main cause is anemia. The iron supplementation tablet (TTD) program is a government effort to reduce the incidence of anemia. The purpose of this study was to describe the level of knowledge and consumption of iron supplement tablets in pregnant women in Pekanbaru City. This research is a descriptive study with a cross-sectional design. The population in this study were pregnant women in the working area of ​​the Pekanbaru City Public Health Center, with a total sample of 225 pregnant women. The results of the study revealed that pregnant women with low knowledge about anemia were 51.6% and those who did not take iron supplements during pregnancy were 66.7%. The conclusion of this study is that there are still pregnant women in Pekanbaru who have low knowledge and do not consume iron supplements during pregnancy, so further research should be carried out regarding the effect of various factors on the level of knowledge about anemia and consumption of blood supplement tablets, so that specific improvements can be made.